Landmarks of Scientific Socialism: "Anti-Duehring" - Engels, Friedrich, 1820-1895; Lewis, Austin, 1865?-1944 (Salt Lake City, UT : Project Gutenberg, 2010)
"Landmarks of Scientific Socialism: 'Anti-Duehring'" by Friedrich Engels is a critical philosophical work written in the late 19th century. The text primarily targets the socialist theories proposed by Eugen Duehring, showcasing Engels's philosophical rebuttals while outlining his and Karl Marx's materialistic philosophy. The work serves as an exploration of the fundamental tenets of socialism, economics, and dialectical materialism, as Engels critiques the idealism and perceived weaknesses in Duehring's arguments. The beginning of "Anti-Duehring" introduces readers to the rise of socialism and critiques Duehring s self-proclaimed intellectual authority within the socialist movement. Engels presents the historical context of socialism's evolution in Europe and emphasizes how economic and social conditions have spurred a collective movement toward socialist ideals. Through a detailed examination, he aims to dismantle Duehring's simplistic philosophical notions and set forth a more scientifically grounded understanding of socialism, reflecting on broader implications like class struggle and economic dynamics in society. This opening segment sets the stage for Engels's ambitions of providing a more rigorous framework for socialist thought, challenging the absolute truths championed by figures like Duehring. (This is an automatically generated summary.)
Release date is 2010-04-09
E-text prepared by Jeannie Howse, Adrian Mastronardi, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/Canadian Libraries (http://www.archive.org/details/toronto)
Keywords: Socialism; Philosophy; Economics; Dialectical materialism; Dühring, E. (Eugen), 1833-1921